The effect of exercise on the risk of metabolic syndrome associated with sleep insufficiency: a cross-sectional study - Chou, Fan-Ya; Chiu, Te-Fa; Huang, Fen-Wei; Hsu, Tai-Yi; Liu, Chien-Yu; Lin, Chin-Han; Huang, Po-Yao; Lin, Kuei-Ming; Wu, Shih-Hao (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Sleep disturbance and insufficient sleep have been linked to metabolic syndrome, increasing cardiovascular disease and mortality risk. However, few studies investigate the joint effect of sleep and exercise on metabolic syndrome. We hypothesized that regular exercise can mitigate the exacerbation of metabolic syndrome by sleep insufficiency.The aim of this study was to investigate whether exercise can attenuate or eliminate the relationship between sleep insufficiency and metabolic syndrome.Method: A total of 6289 adults (mean age = 33.96 years; women: 74.81%) were included in the study, a cross-sectional study conducted based on the results of employee health screening questionnaires and databases from a large healthcare system in central Taiwan. Participants reported sleep insufficiency or not. Self-reported exercise habits were classified into 3 levels: no exercise, exercise < 150 min/week, and exercise ≧ 150 min/week. Multiple logistic regression and sensitivity analyses were conducted to understand the joint associations of sleep patterns and exercise with metabolic syndrome with exposure variables combining sleep duration/disturbances and PA.Results: Compared with the reference group (sufficient sleep), individuals with sleep insufficiency had a higher risk for metabolic syndrome (adjusted odds ratio (AOR) = 1.40, 95% confidence interval (95%CI): 1.01-1.94, p < 0.05) in females aged 40-64 years, but not in other populations. Sleep insufficiency was not associated with the risk of metabolic syndrome among individuals achieving an exercise level of < 150 min/week, and in particular among those achieving ≧ 150 min/week in all populations in our study. This is a provisional file, not the final typeset article Conclusion: Sleep insufficiency was related to a higher risk of metabolic syndrome in female healthcare staff aged 40-64 years. Being physically active with exercise habits in these individuals, the risk of metabolic syndrome was no longer significant.